The Effectiveness of Poster Media to Improve High School Students’ Tsunami Disaster Mitigation Preparedness - M. Edwansyah Rissal; Ali Muhtadi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the effectiveness of poster media in improving the students’ readiness in preparing Tsunami disaster mitigation preparedness. This study uses a quantitative descriptive method with a Quasi-Experimental design. The type used in this research is one group Pretest-Posttest. The research population is students at a state senior high school in Pematang Sawa, class X-XII, in the Academic Year 2021/2022. The sample in this study was 30 people. Data were collected through tests and documentation for three months, from October to December 2021. Then the data were analyzed using descriptive statistics. Analysis of the data used was the paired t-test with the result that there was a significant difference between the pre-test and post-test scores for preparedness in 30 students with p 0.000. Based on these results, it can be concluded that poster media is quite effective in increasing tsunami disaster mitigation preparedness. Further studies are recommended to complete this current study’s weaknesses.